2018
DOI: 10.3390/ijms19072109
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols Derived from Lychee Seed Suppress Aβ (1-42)-Induced Neuroinflammation

Abstract: Amyloid-β (Aβ) is commonly recognized as the most important factor that results in neuronal cell death and accelerates the progression of Alzheimer’s disease (AD). Increasing evidence suggests that microglia activated by Aβ release an amount of neurotoxic inflammatory cytokines that contribute to neuron death and aggravate AD pathology. In our previous studies, we found that lychee seed fraction (LSF), an active fraction derived from the lychee seed, could significantly improve the cognitive function of AD rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 69 publications
1
27
0
Order By: Relevance
“…Our current findings demonstrated that Aβ infussion can induce the expression of iNOS, and supplementation with the tropical fruit juice mixture can attenuate the induction of iNOS expression by Aβ. is observation was supported by previous findings where supplementation with polyphenols derived from lychee seed and resveratrol was able to reduce the iNOS expression in rats following Aβ induction [26,55].…”
Section: Discussionsupporting
confidence: 83%
“…Our current findings demonstrated that Aβ infussion can induce the expression of iNOS, and supplementation with the tropical fruit juice mixture can attenuate the induction of iNOS expression by Aβ. is observation was supported by previous findings where supplementation with polyphenols derived from lychee seed and resveratrol was able to reduce the iNOS expression in rats following Aβ induction [26,55].…”
Section: Discussionsupporting
confidence: 83%
“…PCA2 exhibited anti-inflammatory activity via suppressing CCL-26 production in IL-4-stimulated A549 cells [24] and anti-oxidative activity via modulating the Nrf2 pathway in tert-butyl hydroperoxide-stimulated L0-2 cells [35]. PCA2 has a neuroprotective effect on Aβ-stimulated BV2 cells [36]. However, the detailed mechanism of PCA2's anti-inflammatory and anti-oxidative activity is still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, LPS-stimulated macrophage is a classic model of inflammatory responses in vitro [ 33 ]. Previous studies revealed that PCA2 has the effects of protecting cells from oxidation, inflammation, such as human monocyte macrophages (THP-1) [ 26 ] and L0-2 cells [ 35 ], A549 cells [ 24 ], and BV2 cells [ 36 ], respectively. PCA2 exhibited anti-inflammatory activity via suppressing CCL-26 production in IL-4-stimulated A549 cells [ 24 ] and anti-oxidative activity via modulating the Nrf2 pathway in tert -butyl hydroperoxide-stimulated L0-2 cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…belonging to the Sapindaceae family) and prescribed in various Chinese medical formulas in clinical practice. Our previous studies have clarified that the main components in lychee seed are polyphenols, including rutin, quercetin, catechin, and proanthocyanidins (Tang et al, 2018; Xiong et al, 2020; Zhao et al, 2018). Further study found that these polyphenols in lychee seed (LSP) could inhibit Aβ‐induced apoptosis in neuronal cells and the neuroinflammatory response in microglia via the NF‐κB pathway (Tang et al, 2018; Zhao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have clarified that the main components in lychee seed are polyphenols, including rutin, quercetin, catechin, and proanthocyanidins (Tang et al, 2018; Xiong et al, 2020; Zhao et al, 2018). Further study found that these polyphenols in lychee seed (LSP) could inhibit Aβ‐induced apoptosis in neuronal cells and the neuroinflammatory response in microglia via the NF‐κB pathway (Tang et al, 2018; Zhao et al, 2018). In this study, LSP was prepared as previously described (Wang, Wu, et al, 2017; Wang, Zhang, et al, 2017), then we investigated the protective effect of LSP on BBB integrity.…”
Section: Introductionmentioning
confidence: 99%